Role of matrix metalloproteinases in mitral valve regurgitation: Association between the of MMP‐1, MMP‐9, TIMP‐1, and TIMP‐2 expression, degree of mitral valve insufficiency, and pathologic etiology. Issue 6 (28th March 2022) - Irqsusi, Marc; Mansouri, Azza Labene; Ramaswamy, Anette; Rexin, Peter; Salman, Midhat; Mahmood, Saqib; Mirow, Nikolas; Ghazi, Tamer; Ramzan, Rabia; Rastan, Ardawan J.; Vogt, Sebastian
Abstract: Background: The pathogenesis of mitral valve insufficiency is not yet fully understood. Several studies stressed the role of matrix metalloproteinases (MMPs) in the emergence of valvular pathologies. The primary objective of the present study is to analyze the role of selected MMPs and their inhibitors in mitral valve insufficiency. Patients and Methods: Eighty patients (33 female/47 male, mean age 67 years) underwent cardiopulmonary bypass surgery for mitral valve reconstruction between 2007 and 2015. All patients suffered from mitral insufficiency (MI) Stages iii and iv. When tissue resection was acquired specimens were taken immediately frozen and used for histological examination. Expression of MMP‐1, MMP‐9, tissue inhibitor of metalloproteinase (TIMP)‐1, and TIMP‐2 was examined immunohistochemically and distribution was analyzed in regard to preoperative clinical, echocardiographic, and histopathological findings. Results: A clear correlation between the MMP expression and the MI degree of severity could be shown. The expression of MMPs proved to be high in relation to mild insufficiencies and relatively weak in the case of severe ones. Additionally, the etiology of the MI was considered in the analysis and a significant difference in the expression of MMPs between the mitral valves with endocarditis and the ones featuring a degenerative disease could be shown. Within the group of valves with degenerative diseases, no significant difference could be established between the subgroups (myxoid and sclerosed valves). Conclusion: The increased expression of MMPs and their inhibitors in mild insufficiencies could prove that the molecular changes in the valve precede the macroscopical and thus the echocardiographically diagnosable changes. Hence, new options for early diagnosis and therapy of MIs should be examined in further studies, respectively. Herein, the correlation of the MMP blood levels with MMP tissue expression should be addressed for surgical therapeutical decisions.